Autophagy Limits Inflammasome During Chlamydia pneumoniae Infection - Crother, Timothy R.; Porritt, Rebecca A.; Dagvadorj, Jargalsaikhan; Tumurkhuu, Gantsetseg; Slepenkin, Anatoly V.; Peterson, Ellena M.; Chen, Shuang; Shimada, Kenichi; Arditi, Moshe (Frontiers in Immunology, 2019)
Autophagy can either antagonize or promote intracellular bacterial growth, depending on the pathogen. Here, we investigated the role of autophagy during a pulmonary infection with the obligate intracellular pathogen, Chlamydia pneumoniae (CP). In mouse embryonic fibroblasts or macrophages, deficiency of autophagy pathway components led to enhanced CP replication, suggesting that autophagy exerts a bactericidal role. However, in vivo, mice with myeloid-specific deletion of the autophagic protein ATG16L1 suffered increased mortality during CP infection, neutrophilia, and increased inflammasome activation despite no change in bacterial burden. Induction of autophagy led to reduced CP replication in vitro, but impaired survival in CP-infected mice, associated with an initial reduction in IL-1β production, followed by enhanced neutrophil recruitment, defective CP clearance, and later inflammasome activation and IL-1β production, which drove the resulting mortality. Taken together, our data suggest that a delicate interplay exists between autophagy and inflammasome activation in determining the outcome of CP infection, perturbation of which can result in inflammatory pathology or unrestricted bacterial growth.